2017
DOI: 10.1002/lary.26814
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of complicated airway foreign body extraction

Abstract: 4. Laryngoscope, 128:490-495, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 11 publications
3
14
2
1
Order By: Relevance
“…This means that it is not RULE: “higher repetition rate- less mortality”. It is agreed with statement that surgeon and hospital volume did not significantly correlate with higher complication rates ( 53 ).…”
Section: Discussionsupporting
confidence: 78%
“…This means that it is not RULE: “higher repetition rate- less mortality”. It is agreed with statement that surgeon and hospital volume did not significantly correlate with higher complication rates ( 53 ).…”
Section: Discussionsupporting
confidence: 78%
“…This finding was also not comparable with the results of previous studies. 15,16 The retrospective design is the most important limitation of our study. Similar to previous BLW studies, since the exact definition and criteria of the BLW method are lacking, it is difficult to reach a firm conclusion that the BLW method is a risk factor for FBA.…”
Section: Discussionmentioning
confidence: 99%
“…A slight male predominance was observed in our study 322 (57.5%) with a ratio of 1.4:1. Other studies showed that FBA was more common amongst boys than girls with a range of 54.8%-81.8% [8,9,16,17,22,23,24,25,26]. It's no secret that most boys are active, loud, rambunctious, have mischievous behaviour, and are adventurous in nature.…”
Section: Discussionmentioning
confidence: 99%